Sedative Effects of Intraperitoneal Diazepam in Mice - Vania, Marsha; Sari, Shinta Dewi Permata; Siswitono, Bambang; Stujanna, Endin Nokik (International Journal of Integrated Health Sciences, 2023)
Objectives: To determine the effectiveness of Diazepam in comparison with Phenobarbital.Methods: Twenty-seven male Swiss Webster mice were used and randomly divided into three groups of negative control (NS), positive control (Phenobarbital), and diazepam group. Two tests were performed on these group: the traction Test and the Fireplace Test. Pupillary diameter was also observed.Results: A significant difference based on the Kruskal - Wallis statistical test was observed between the positive control and the diazepam group (<0.05) in the traction test, which was also true for the fireplaced test (p<0.05). The pupillary diameter in the test animals in the positive control and diazepam group was not statistically significant (p>0.05).Conclusion: Diazepam has a better sedative effect than Phenobarbital. The sedative effect produced by Diazepam is stronger, with faster onset and longer half-life than the Phenobarbital the positive control. However, different test methods and comparisons should be sought to support this conclusion.